The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.12911/22998993/140478
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation Needs in Ukraine According to Current Aridity Level

Abstract: Global climate change has led to significant shifts in local climatic conditions of Ukraine with the trend to aridity aggravation. Sustainable crop production is at risk due to the aridity level increase. The study is aimed to evaluate aridity index in Ukraine (on the whole country and individual regions' scales) and the needs in irrigation using hydro-meteorological data of the key regional stations for the periods of 1961-1990 and 2010-2020. The results of hydro-meteorological evaluation were supported by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
1
8
0
1
Order By: Relevance
“…The main goal of this study is to find out the best approach among common regression analysis techniques, used nowadays in crops' yield modeling, for the yield prediction of major crops, cultivated in the South of Ukraine, by the volumes of their water use. Such models are of great importance for sustainable crop production in the region, as it is one that belongs to the area of highly risky agriculture because of constant lack of natural water supply [14].…”
Section: Introductionmentioning
confidence: 99%
“…The main goal of this study is to find out the best approach among common regression analysis techniques, used nowadays in crops' yield modeling, for the yield prediction of major crops, cultivated in the South of Ukraine, by the volumes of their water use. Such models are of great importance for sustainable crop production in the region, as it is one that belongs to the area of highly risky agriculture because of constant lack of natural water supply [14].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, Europe and Asia cover 78% of the total global wheat grain production [FAO-Stat, 2020]. Current global food crisis, connected with climate change and simultaneous deficit of natural resources and their deterioration (e.g., soil degradation, freshwater deficit, unfavorable weather phenomena), under the constant trend to the increase in global population implies a forecasted wheat consumption increase by 132 M mt/ year by 2050 [Lykhovyd, 2021;Erenstein et al, 2022]. To face the challenge of global starvation, steps should be taken to increase wheat production.…”
Section: Introductionmentioning
confidence: 99%
“…The modern climate in most of the territory of Ukraine is semi-arid. It was found that 46.05% of acreage cannot provide sustainable crop production without irrigation, and 42.65% need irrigation to grow plants with high water use (Lykhovyd, 2021). The need to increase the production of vegetables against the background of a constant decline in soil quality and climate change to a more arid one, causes elevated interest in finding new measures that would provide plants with sufficient water.…”
Section: Introductionmentioning
confidence: 99%